A Numerical Approach to Study the Steady State Heat Transfer Characteristics of an Annular Porous Heat Exchanger. Issue 4 (August 2020) - Ghosh, Subhankar; Senthilkumar, S.; Deep, Dewanshu; Bharanitharan, K. J.
Abstract: Heat exchangers are one of the most heavily studied devices and extensive work has been performed over the years to increase their effectiveness. The present work investigates the heat transfer characteristics of an APHE (annular porous heat exchanger) in terms of different parameters. A modified design for the APHE is proposed, which resembles a conventional double pipe heat exchanger, with the annular portion of the outer pipe filled with a specific type of porous medium in order to intensify the heat transfer process. Commercial CFD package ANSYS Fluent has been utilized to investigate the performance of the proposed design numerically. Introduction of porous medium induces an increase in pressure loss which is undesirable; hence, a trade-off is present between hydrodynamic and thermodynamic performance. In the present work different inlet parameters have been modified such as different values of porosity (70% to 90%), different inlet velocities of hot fluid (1 m/s to 9 m/s), different inlet velocities of cold fluid (5 mm/s to 25 mm/s), and different inlet temperature of hot fluid (400 K to 480K), and their effects on the outlet parameters have been studied. The change in heat transfer has been presented quantitatively along with other significant parameters such as mass flow rate, pressure drop and hot gas outlet temperature. These results have been compared with the values for conventional heat exchangers in order to establish the effectiveness of APHE.